2019
DOI: 10.1371/journal.ppat.1007953
|View full text |Cite
|
Sign up to set email alerts
|

Novel lactate dehydrogenase inhibitors with in vivo efficacy against Cryptosporidium parvum

Abstract: Cryptosporidium parvum is a highly prevalent zoonotic and anthroponotic protozoan parasite that causes a diarrheal syndrome in children and neonatal livestock, culminating in growth retardation and mortalities. Despite the high prevalence of C . parvum , there are no fully effective and safe drugs for treating infections, and there is no vaccine. We have previously reported that the bacterial-like C . parvum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 30 publications
(51 reference statements)
2
26
0
Order By: Relevance
“…1 ). Paromomycin at 800 μM was used as the inhibitor control and all experimental data were normalized with DMSO-treated wells (0% inhibition) and inhibitor control (100% inhibition) wells as previously reported ( Li et al, 2019 ). On the other hand, we found 4 compounds (JS-1-09, JS-2-20, JS-2-35 and JS-2-49) that had significant inhibitory effect against the growth of T. gondii in vitro at 20 μM final concentration ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…1 ). Paromomycin at 800 μM was used as the inhibitor control and all experimental data were normalized with DMSO-treated wells (0% inhibition) and inhibitor control (100% inhibition) wells as previously reported ( Li et al, 2019 ). On the other hand, we found 4 compounds (JS-1-09, JS-2-20, JS-2-35 and JS-2-49) that had significant inhibitory effect against the growth of T. gondii in vitro at 20 μM final concentration ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Among all the compounds tested, only GMG-1-09 had in vitro efficacy against C. parvum with an anti- Cryptosporidium IC 50 concentration that was 14-fold lower than its cytotoxicity IC 50 concentration in a human intestinal cell line (HCT-8). We used paromomycin as a positive control that has an anti- Cryptosporidium IC 50 of 450 μM ( Li et al, 2019 ) and has been shown to be non-toxic to human cells at concentrations higher than 1000 μM ( Gargala et al, 2000 ; Downey et al, 2008 ). Comparatively, compound GMG-1-09 was efficacious against C. parvum at a much lower concentration (IC 50 = 32.34 μM) than paromomycin.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ruminococcus can produce acetic acid, formic acid, and a small amount of lactic acid (42). Previous research has indicated that short-chain fatty acid including formic acid, acetic acid play a critical role in regulating the balance of gut microbiota and maintaining morphology and function of intestinal epithelial cells (43,44). Moreover, the short-chain fatty acid regulates energy intake by the brain-gut axis (45).…”
Section: Discussionmentioning
confidence: 99%